Evidence of Electron Density Enhancements in the Post‐Apoapsis Sector of Enceladus' Orbit. Issue 6 (12th June 2020) - Persoon, A. M.; Kurth, W. S.; Gurnett, D. A.; Groene, J. B.; Smith, H. T.; Perry, M. E.; Morooka, M. W.; Ye, S.
Abstract: Enceladus' plume is the dominant source of neutrals and plasma in Saturn's magnetosphere. The plasma results from the ionization of icy particles and water vapor, which are vented into Saturn's inner magnetosphere through fissures in Enceladus' southern polar region. These fissures are subjected to tidal stresses that can vary as Enceladus moves in a slightly eccentric orbit around Saturn. Plume activity and brightness have also been shown to vary with the moon's orbital position, reaching a maximum when Enceladus is farthest away from Saturn in its orbit (the Enceladus orbital apoapsis). In this paper we will show that temporal variations in the thermal electron density distribution correlate with the position of Enceladus in its orbit around Saturn, with the strongest density enhancements in the vicinity of Enceladus when the moon is in the post‐apoapsis sector of its orbit. Key Point: There is evidence of enhanced electron densities in the near‐moon environment when Enceladus is in the post‐apoapsis sector of its orbit